INDIAN-AMERICANS IDENTITY IN “THIS BLESSED HOUSE” SHORT STORY - Maulida, Lifia; Farkhan, Muhammad; Djohar, Hasnul Insani (PARADIGM: Journal of Language and Literary Studies, 2022)
This research discusses the identity of indian immigrants especially the main characters, Sanjeev and Twinkle, in the short story “This Blessed House” by Jhumpa Lahiri. The theory used in this research is cultural studies theory by Stuart Hall and combining with character and characterization theory of fiction. This research focuses on the habits of an indian immgirants who lived in Connecticut, the United states, and also the factors that made the  main characters have different identity. The husband has a stable identity and trying to maintain Indian culture while his wife acting like an American. As Twinkle shows that she loses her origin identity, which is indian, because she does not preserve her identity strongly and Sanjeev succeeds to carry his Indian identity to their household because Sanjeev has a strong Indian culture. Compared to Twinkle, Sanjeev was more recently living in America. So Twinkle has been exposed to American culture longer than Sanjeev.